Antibody mediated therapy targeting CD47 inhibits tumor progression of hepatocellular carcinoma. Issue 2 (1st May 2015) - Xiao, Zhenyu; Chung, Haniee; Banan, Babak; Manning, Pamela T.; Ott, Katherine C.; Lin, Shin; Capoccia, Benjamin J.; Subramanian, Vijay; Hiebsch, Ronald R.; Upadhya, Gundumi A.; Mohanakumar, Thalachallour; Frazier, William A.; et al.
Highlights First time demonstrating that CD47 blockade has anti-tumor effects against HCC. In vitro CD47 blockade results in increase in phagocytosis of HCC cells. In vivo CD47 blockade inhibits HCC tumor growth in hetero/orthotopic models. CD47mAb400 is clearly more efficacious than widely-investigated B6H12 antibody.